Implementation of Islamic Education Evaluation Principles Based On the Qur'an and Hadith at State Elementary School 21 Pagar Alam: Implementation of Islamic Education Evaluation Principles Based On the Qur'an and Hadith at State Elementary School 21 Pagar Alam - Darmanto; Era Afriza; Ali Imron; Suharmon (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
This study aims to analyze the application of Islamic educational evaluation principles based on the Qur'an and Hadith at SD Negeri 21 Pagar Alam. The main issue raised is how Islamic evaluative values, such as justice ('adl), honesty (shidq), and responsibility (amanah), are implemented in the process of assessing student learning outcomes. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results indicate that teachers at SD Negeri 21 Pagar Alam have attempted to integrate Islamic evaluation values ​​into their teaching practices, particularly in assessing students' attitudes and spirituality. However, their implementation still faces challenges related to consistency and teachers' understanding of evaluation principles rooted in the Qur'an and Hadith. These findings emphasize the importance of ongoing training for educators to internalize religious values ​​in educational evaluation. Thus, evaluation not only assesses academic outcomes but also directs the development of character and noble morals in students in accordance with the goals of Islamic education. Keywords: Evaluation Of Islamic Education, Al-Quran And Hadisth, Islamic Values, Authentic Assessment, Student Character